2016
DOI: 10.1007/s11136-016-1329-z
|View full text |Cite
|
Sign up to set email alerts
|

Stigma as a key determinant of health-related quality of life in Parkinson’s disease

Abstract: Purpose People with Parkinson's disease (PD) may experience stigma due to their visible features of movement and communication difficulties. This paper aimed to examine the role of experienced stigma in health-related quality of life (QOL), after controlling for personal and clinical characteristics. Methods This is a preliminary analysis of a subset of baseline data from the Social Self-Management of Parkinson's Disease Study (SocM-PD), an ongoing 3-year prospective cohort study. 73 people with PD (Mage = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
64
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 29 publications
9
64
1
1
Order By: Relevance
“…Although causality cannot be determined from crosssectional studies, the results suggest that when patients perceive greater difficulty in their daily activities, selfdepreciation could increase. Such a relationship was also found by Ma et al 32 We found no association between stigma and scoring on the MDS-UPDRS III scale, which evaluates motor difficulties objectively using a third evaluator, which demonstrates the importance of patient self-perception. Thus, although motor symptoms, which had been objectively assessed by a neurologist, were not associated with patient self-stigma, patient perception of difficulties with daily activities was associated with selfstigma, independently of depressive symptoms or other characteristics of the disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although causality cannot be determined from crosssectional studies, the results suggest that when patients perceive greater difficulty in their daily activities, selfdepreciation could increase. Such a relationship was also found by Ma et al 32 We found no association between stigma and scoring on the MDS-UPDRS III scale, which evaluates motor difficulties objectively using a third evaluator, which demonstrates the importance of patient self-perception. Thus, although motor symptoms, which had been objectively assessed by a neurologist, were not associated with patient self-stigma, patient perception of difficulties with daily activities was associated with selfstigma, independently of depressive symptoms or other characteristics of the disease.…”
Section: Discussionsupporting
confidence: 87%
“…Another study showed that stigma was a determinant of depression, which was a predictor of the quality of life. 31 Ma et al, 32 in a study of PD patients, found that those with more depressive symptoms reported more stigma, especially self-stigma, which appears to be of greater and more direct importance in quality of life than social stigma. Our sample likely diverged from these results due to its relatively low level of depressive symptoms, since approximately 70% of the patients scored up to nine on the HADS depression subscale, whose suggested cut-off for a major depressive episode is 10/ 11.…”
Section: Discussionmentioning
confidence: 99%
“…PD patients in a review of a number of studies experienced impact on the quality of their interactions with others, producing a retreat from the social sphere [38]. Stigma has been found to predict negatively for QoL in PD [39]. When it is considered that speech problems in MSA and PSP are more severe and have an earlier onset and the conditions are overall less responsive to medication, these factors are especially important to consider in AP [40].…”
Section: Discussionmentioning
confidence: 99%
“…Patients who cannot cope with social life due to their symptoms and who withdraw from society will have to live alone in their private world. Studies showed that higher stigma scores were related to more severe PD symptoms (35). Nowinski et al showed that the stigma T-score was 48.39 ± 6.62 in PD cases (36).…”
Section: Discussionmentioning
confidence: 99%